2018
DOI: 10.1007/s00248-018-1251-8
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase−Hemicellulase Activities and Bacterial Community Composition of Different Soils from Algerian Ecosystems

Abstract: Soil microorganisms are important mediators of carbon cycling in nature. Although cellulose- and hemicellulose-degrading bacteria have been isolated from Algerian ecosystems, the information on the composition of soil bacterial communities and thus the potential of their members to decompose plant residues is still limited. The objective of the present study was to describe and compare the bacterial community composition in Algerian soils (crop, forest, garden, and desert) and the activity of cellulose- and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…This nding is consistent with that of Cheng et al (2018) and who found that amino acid metabolism and carbohydrate metabolism are the main metabolic functions by PICRUSt predictions [37][38] . These results suggested that amino acid metabolism and carbohydrate metabolism are main bacterial functions in soil, not only in halophyte vegetation soil but also in other soil types [39][40][41] . Chaudhary et al (2018) indicated that the microbial functional gene abundance was affected by different halophyte vegetation types 42 .…”
Section: Discussionmentioning
confidence: 83%
“…This nding is consistent with that of Cheng et al (2018) and who found that amino acid metabolism and carbohydrate metabolism are the main metabolic functions by PICRUSt predictions [37][38] . These results suggested that amino acid metabolism and carbohydrate metabolism are main bacterial functions in soil, not only in halophyte vegetation soil but also in other soil types [39][40][41] . Chaudhary et al (2018) indicated that the microbial functional gene abundance was affected by different halophyte vegetation types 42 .…”
Section: Discussionmentioning
confidence: 83%
“…This results also implied that the rumen fluid had specialized enzymes secreted by the indigenous microorganisms for lignocellulose degradation, the presence of this microbial community have been detected through several modern molecular techniques [29]. Several investigations in the potential microorganism of rumen fluid were carried out, a significant reduction in content was achieved on cellulose in 72 h treatment as much as 23%, and it was found that the dominated microorganism was Firmicutes, and this particular group of bacteria are the potential cellulase producer [30], [31]. Another investigation also showed that the particular microorganism has the ability to degrade lignin due to extracellular peroxidase [32].…”
Section: Figurementioning
confidence: 88%
“…3Bio Journal of Biological Science, Technology and Management 2(2): [30][31][32][33][34][35][36][37][38] Ilhamy et al…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, metagenomic studies showed that genes encoding cellulases, xylanases, cellobiohydrolases, endoglucanases and cellulose-binding proteins were detected in rice root endophytic bacterial communities (Sessitsch et al, 2012). Houfani et al compared the associated bacterial communities of several ecosystems (agricultural, garden, desert, among others) and determined functions in silico and in vitro, highlighting the presence of a higher proportion of genes encoding cellulases, hemicellulases and pectinases assigned to forest soils, in which there is more lignocellulosic materials available for degradation (Houfani et al, 2019).…”
Section: Cellulases Pectinases and Xylanasesmentioning
confidence: 99%